Strategi Peningkatan Kesadaran Tata Kelola Pembangunan Kependudukan Kolaboratif (Program Kampung KB (Keluarga Berkualitas) Di Kabupaten Siak Tahun 2023 - Lahamid, Sadriah; Juliana, Septa; Astuti, Daharmi; Ningsih, Fardina (Universitas Pahlawan Tuanku Tambusai, 2024)
The demographic bonus that will hit Indonesia in 2030-2040, where the productive age population (15-64 years) is greater than the non-productive age (65 years and over) more than 60% of the total population of Indonesia. Productive age is expected to contribute positively to development rather than being a population disaster for development, including in Siak District. A comprehensive strategy is needed so that when the demographic bonus occurs, the government is ready with regulations and human resources for managers and objects of population development programs. The Siak Regent's strategy to increase awareness by issuing the Siak Regent Decree number: 213/HK/KPTS/2023 concerning the Establishment of Quality Family Villages at the Village and Kelurahan levels in Siak District in 2023 has not been implemented properly, based on this policy, 131 KB villages should have been formed in Siak District in 2023. This happens because stakeholders do not understand the benefits of population development governance. Synergy is needed in the implementation of the KB Village program with a collaborative Governance pattern, so that it becomes a solution to population development in Siak district. Research using qualitative methods, directly interacting with the object of research.